PEMBERDAYAAN STAKEHOLDER SEKUNDER TERHADAP PENGEMBANGAN BATIK TULIS DI SURAKARTA - Sudarwati, Siti Maryam dan (MAJALAH ILMIAH GEMA, 2014)
Batik has been like the identity of the city of Solo. Results Solo batik production was already in exports to foreign countries. As a city that is synonymous with batik , Solo has some areas of batik production centers. In fact, Mr. President Susilo Bambang Yudhoyono launched on October 2 as the Batik Day. It was two years ago also, world recognized  batik as an Indonesian  property rights, in this case Mr. President Susilo Bambang Yudhoyono is one of the stakeholders that the government is able to increase the empowerment Solo batik through the worldwide recognition of Indonesian batik is the property of.Issues that will be examined in this study were 1) how far the efforts made by the secondary stakeholders to develop in Surakarta batik Write 2) how empowerment stakeholdersekunderuntuk develop in Surakarta batik Write, review of aspects of marketing?The  objectives  are  1)  to  know  the  efforts  that  have  been  made  for  the development  of  the  stakeholdersekunder   Write  in  Surakarta  batik  2)  to  empower secondary stakeholders in marketing activities in Surakarta batik Write.This study used a qualitative approach. Location of the research was conducted in Surakarta.   The population in this study is a secondary stakeholders. The samples with snowball sampling, data sources obtained from stakeholders, statistical data, literature,  and informants  with in-depth  interviewing  techniques,  documentation  and observation. Data analysis was performed interactively, following the concept of Miles & Huberman given and Spradley. Keywords : secondary stakeholders, empowerment, marketing